Inter-rater and intra-rater reliability and agreement of echocardiographic diagnosis of rheumatic heart disease using the World Heart Federation evidence-based criteria. Issue 2 (24th June 2019) - Remenyi, Bo; Carapetis, Jonathan; Stirling, John W; Ferreira, Beatrice; Kumar, Krishnan; Lawrenson, John; Marijon, Eloi; Mirabel, Mariana; Mocumbi, A O; Mota, Cleonice; Paar, John; Saxena, Anita; et al.
Abstract : Objective: Different definitions have been used for screening for rheumatic heart disease (RHD). This led to the development of the 2012 evidence-based World Heart Federation (WHF) echocardiographic criteria. The objective of this study is to determine the intra-rater and inter-rater reliability and agreement in differentiating no RHD from mild RHD using the WHF echocardiographic criteria. Methods: A standard set of 200 echocardiograms was collated from prior population-based surveys and uploaded for blinded web-based reporting. Fifteen international cardiologists reported on and categorised each echocardiogram as no RHD, borderline or definite RHD. Intra-rater and inter-rater reliability was calculated using Cohen's and Fleiss' free-marginal multirater kappa (κ) statistics, respectively. Agreement assessment was expressed as percentages. Subanalyses assessed reproducibility and agreement parameters in detecting individual components of WHF criteria. Results: Sample size from a statistical standpoint was 3000, based on repeated reporting of the 200 studies. The inter-rater and intra-rater reliability of diagnosing definite RHD was substantial with a kappa of 0.65 and 0.69, respectively. The diagnosis of pathological mitral and aortic regurgitation was reliable and almost perfect, kappa of 0.79 and 0.86, respectively. Agreement for morphological changes of RHD was variable ranging from 0.54 to 0.93 κ. Conclusions: The WHF echocardiographic criteria enable reproducible categorisation of echocardiograms as definite RHD versus no or borderline RHD and hence it would be a suitable tool for screening and monitoring disease progression. The study highlights the strengths and limitations of the WHF echo criteria and provides a platform for future revisions.